2020
DOI: 10.4149/av_2020_209
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective review and current knowledge on the occurrence of West Nile virus in mosquito vectors, reservoirs and hosts in Slovakia (Central Europe)

Abstract: West Nile virus (WNV) is a mosquito-borne flavivirus (the genus Flavivirus, the family Flaviviridae). It belongs

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…This is the first scientific report showing the potential of the burrows of medium-sized carnivores to serve as wintering places for this particular mosquito species. This finding also suggests a role played by the burrows in the ecology of Culex-transmitted arboviruses (Brugman et al, 2018;Korytár et al, 2020).…”
Section: Discussionmentioning
confidence: 61%
“…This is the first scientific report showing the potential of the burrows of medium-sized carnivores to serve as wintering places for this particular mosquito species. This finding also suggests a role played by the burrows in the ecology of Culex-transmitted arboviruses (Brugman et al, 2018;Korytár et al, 2020).…”
Section: Discussionmentioning
confidence: 61%
“…We found out that MIR of WNV in mosquitoes caught in Lučenec surrounding ( Figure 1 ) was three-fold higher than MIR in mosquitoes collected in the Bratislava region, where two symptomatic WNV cases were diagnosed previously [ 21 , 23 ]. Furthermore, WNV has been diagnosed in a bird’s carcass in the neighboring district of Lučenec, Rimavská Sobota and TBEV antibodies were detected by the enzyme-linked immunosorbent assay (ELISA) and a plaque reduction neutralization test (PRNT) in sheep and goats in the farm Hradište ( Figure 1 ) [ 22 , 28 ]. For this reason, it is highly probable the WNV and USUV cases might be overlooked and/or misdiagnosed as TBEV infections.…”
Section: Overlapping Area Of Co-circulating Wnv Usuv and Tbevmentioning
confidence: 99%
“…In Slovakia, WNV was first isolated from Aedes cantans mosquitoes between the years 1960 and 1972 [7]. After that, serological studies showed WNV circulation in horse and bird populations [8][9][10][11]. The phylogenetic analysis of whole-genome strains isolated from the brain of dead raptors showed relatedness to WNV lineage 2 [12].…”
Section: Introductionmentioning
confidence: 99%
“…BLAST analysis of a partial NS5 gene showed almost 100% identity with strains from Germany, Italy, and Austria [13]. The first confirmed autochthonous case of West Nile fever was diagnosed in the late summer of 2019, in a man infected by mosquitoes in the area of western Slovakia [11,14,15].…”
Section: Introductionmentioning
confidence: 99%